The seroprevalence trend of Helicobacter pylori infection in Gombe, Nigeria: a 5-year retrospective study - Ibrahim, Yakubu; Famoriyo, Lateef; Muhammad Sani, Fatima; Basri, Nurul Iftida; Jamil Mohd, Amilia Afzan; Abdurrahman, Muhammad Shuaibu; Abdullahi, Idris (Zagazig University, Faculty of Medicine, 2022)
Background: Helicobacter pylori (H. pylori) infection is highly prevalent globally and half of the world’s population are carrying the pathogen with infection rates higher in low and middle-income countries. The study aim was to retrospectively determine the seroprevalence trend of H. pylori infection among patients suspected to have dyspepsia and identify socio-demographic determinants for H. pylori seropositivity. Methods: This retrospective study was conducted at the State Specialist Hospital, Gombe, Nigeria from January 2015 to December 2019. A total of 11,935 patients were included in the study and lateral flow immunochromatographic immuno assay was used to screen for total anti H. pylori antibodies. Results: The overall sero-prevalence of H. pylori infection was 58.9%. There was significant association between H. pylori seroprevalence rate and age of subjects, (χ2=20.86; p < /em><0.001). The study subjects between the age group 31-40 years had the highest seroprevalence, 62.3%. The seroprevalence of H. pylori was associated with sex of subjects (χ2=39.73; p < /em><0.0001). The seroprevalence trend of H. pylori was highest in 2016 with 61%, followed by 2019 (60.8%), then 2017 (59.3%), 2018 (54.7%) and least in 2015 (50.5%). Conclusion: Findings from the study showed a steady rise in the seroprevalence of H. pylori infection over the five years of study. Furthermore, H pylori infection appears to be higher among adults in their most productive years. Based on these, it is needful to develop strategies for eradication of the infection, encourage health education by creating awareness towards improving environmental and household sanitation, water, personal and food hygiene.